Resilience anchors for children in an out-of-home care institution during and after COVID-19 - Malindi, Macalane Junel; Hay, Johnnie (Frontiers in Psychology, 2023)
Growing numbers of children of all ages grow up in out-of-home care institutions due to personal and socioecological risk variables that destabilized their families of origin. In the aftermath of the COVID-19 pandemic which disrupted lives and development, there is particular interest in how children who grow up in out-of-home care institutions cope and develop. This paper reports on the findings of a study that sought to document anchors of resilience in children in a care institution run by a non-governmental, church-based welfare organization in one of the central provinces of South Africa. In line with recent developments in childcare, the organization mainly functions via smaller child and youth group homes across the province (compared to bigger children's homes in the past). In our qualitative, phenomenological study, we used the participatory, child-friendly, and less intrusive drawand-write technique to generate data. We asked the 20 participating children of one of these group homes to make drawings that mirror their lives, and to write paragraphs in which they described their drawings. All were school-going children in care, aged from 12 to 19. There were 11 girls and 9 boys in the study, and one of these identified as "other". The grades ranged from 7 to 12 and they spoke the African languages of Afrikaans, Sesotho, Setswana and IsiXhosa. We used inductive content analysis to process the data, and the findings indicate that, notwithstanding personal and socioecological risks during and after the COVID-19 pandemic, the resilience of the participants was anchored by a number of common personal strengths as well as socioecological resources.